Laser shock peening and its effects on microstructure and properties of additively manufactured metal alloys: a review. (17th June 2020) - Munther, Michael; Martin, Tyler; Tajyar, Ali; Hackel, Lloyd; Beheshti, Ali; Davami, Keivan
Abstract: This review paper discusses the recent progress in laser shock peening (LSP) of additively manufactured (AM) parts. LSP is an advanced post-processing technique that optimizes the service lives of critical components for various applications by inducing severe plastic deformation accompanied by the enhancement of surface properties in treated materials. Material improvement is enabled through the generation of high-density dislocations, grain refinement, and beneficial phase transformations. These mechanisms produce high magnitude compressive residual stresses which harden treated regions to depths exceeding 1 mm. However, a major roadblock for AM parts stems from the various fabrication processes themselves where detrimental tensile residual stresses are introduced during part manufacturing, along with near-surface voids and cracks, all of which severely limit their applications. In addition to post-fabrication heat treatment that is typically required to homogenize the microstructure and relieve the residual stresses of AM parts, post-processing surface treatments have also been developed to manipulate the residual stresses of AM materials. Tensile residual stresses generated during manufacturing affect the fatigue life of AM material negatively and could potentially surpass the material's yield strength, resulting in acute geometric distortion. Recent studies have shown the potential of LSP to mitigate these stresses, modify the mechanical properties of the AM parts, and to close near-surface voids and cracks. Furthermore, the thermal stability of favorable microstructural modifications in laser peened AM parts, which allows for its use in high temperature environments, is not well understood and is currently limiting its effective utilization in these scenarios. The main goal of this review is to provide the detailed insight needed for widespread acceptance of this technique as a post-processing method for AM materials.